Childhood cyanotic congenital heart disease and iron deficiency (Eurasian Medical Research Periodical, 2023)
Inadequate tissue oxygenation results from cyanotic congenital heart disease. In an effort to increase red blood cell bulk, which will boost oxygen supply to the tissues, this in turn drives greater erythropoietin release from the kidneys. As a result of the prolonged erythropoiesis, polycythemia and frequently iron shortage arise from the depletion of iron reserves. Blood viscosity is enhanced and there is a propensity for bleeding thrombosis in both polycythemia and iron shortage